2017
DOI: 10.3892/ol.2017.7189
|View full text |Cite
|
Sign up to set email alerts
|

Combined pitavastatin and dacarbazine treatment activates apoptosis and autophagy resulting in synergistic cytotoxicity in melanoma cells

Abstract: Abstract. Melanoma is an aggressive skin cancer and its incidence is increasing faster than any other type of cancer. Whilst dacarbazine (DTIC) is the standard chemotherapy for metastatic melanoma, it has limited success. Statins, including pitavastatin, have been demonstrated to have a range of anticancer effects in a number of human cancer cell lines. The present study therefore explored the anti-cancer activity of combined DTIC and pitavastatin in A375 and WM115 human melanoma cells. Cell survival assays de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…In cancer cells, lovastatin induced autophagy by up‐regulating LC3‐II (Shi, Felley‐Bosco, Marti, & Stahel, 2012), and atorvastatin through LC3‐I to LC3‐II conversion (Hu et al, 2018). In the same way, pitavastatin stimulated autophagy in melanoma after also increasing LC3‐II levels (Al‐Qatati & Aliwaini, 2017). Interestingly, statins trigger autophagy not only in tumoural tissues.…”
Section: Role Of Statins In the Autophagy Responsementioning
confidence: 87%
“…In cancer cells, lovastatin induced autophagy by up‐regulating LC3‐II (Shi, Felley‐Bosco, Marti, & Stahel, 2012), and atorvastatin through LC3‐I to LC3‐II conversion (Hu et al, 2018). In the same way, pitavastatin stimulated autophagy in melanoma after also increasing LC3‐II levels (Al‐Qatati & Aliwaini, 2017). Interestingly, statins trigger autophagy not only in tumoural tissues.…”
Section: Role Of Statins In the Autophagy Responsementioning
confidence: 87%
“…The effect of compound 6 on the cell cycle profile of cancer cells was determined according to a previous protocol (17). Briefly, cells were seeded at 3–4×10 5 cells per 6-cm dish and allowed to settle for 24 h. Log-phase cultures were exposed to compounds 5–7 (0 to 100 µM) or vehicle for 48 h. Cells were trypsinized, washed with PBS and fixed overnight in 95% ethanol at 4°C, and subjected to RNase treatment and stained for 30 min at room temperature with propidium iodide (PI; 500 µg/ml; Sigma-Aldrich; Merck KGaA).…”
Section: Methodsmentioning
confidence: 99%
“…The lysates were collected, and the protein concentrations were determined using Bradford's reagent (Bio-Rad Laboratories, Inc.), according to the manufacturer's instructions and using albumin as a standard. A total of 20 µg protein was separated by 8–15% SDS-PAGE, and transferred to a Hybond ECL nitrocellulose membrane (GE Healthcare, Chicago, IL, USA) (17). Following blocking for 1 h at room temperature with PBS containing 0.05% Tween-20 and 5% powdered skim milk, membranes were incubated overnight with primary antibodies (1:1,000) at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Autophagic cell death has been reported to be highly effective in the therapy of melanoma [ 29 ]. Moreover, it has been shown that activation of apoptosis and autophagy can result in a synergistic cytotoxicity in melanoma cells [ 30 ].…”
Section: Resultsmentioning
confidence: 99%